AGE DIFFERENCES AND ADJUSTMENT AMONG FRESHMEN AT ONE SELECTED PUBLIC UNIVERSITY - Peter JO Aloka (Social Sciences and Education Research Review)
Freshmen in Kenyan universities face numerous adjustment challenges in their transitioning to higher education. This study examined age differences and adjustment among freshmen at one university in Kenya. Student Integration Theory was chosen to inform this study. The study adopted a cross-sectional survey design. The research participants comprised 213 freshmen in one public university. The quantitative data from questionnaire was analyzed by using Analysis of Variance (ANOVA) statistical test. The findings of the study indicate that older students showed better adjustments as compared to younger students, thus age freshmen determines their adjustment. This study concludes that age is a very significant factor which affects adjustments among freshmen at universities. It is recommended that counselors at universities should develop unique orientation programs which suit younger students who join the university.